Fast 3D Node Localization in Multipath for UWB Wireless Sensor Networks Using Modified Propagator Method - Hong Jiang; Chang Liu; Yu Zhang; Haijing Cui (International Journal of Distributed Sensor Networks)
A fast three-dimensional (3D) node localization algorithm in multipath for ultra-wideband (UWB) wireless sensor networks is developed. The algorithm employs a modified propagator method (MPM) for time delay estimation and then uses a marriage algorithm of 3D Chan and Taylor for range-based multilateral localization and node position computation. In the proposed algorithm, the traditional propagator method (PM) for direction-of-arrival (DOA) estimation is extended to frequency-domain time-of-arrival (TOA) estimation in multipath, which can effectively measure the distance between an unknown sensor node and an anchor node. MPM algorithm requires neither spectral searching nor covariance matrix estimation and its eigenvalue decomposition, which reduces the computational complexity. The marriage location algorithm enhances the robustness and accuracy of node localization. The simulations validate the effectiveness of the proposed algorithm in locating multiple unknown nodes of UWB wireless sensor networks in 3D space.